First Pediatric Pyeloplasty Using the Senhance® Robotic System-A Case Report - Juergen Holzer; Peter Beyer; Florian Schilcher; Clemens Poth; Dietmar Stephan; Christian von Schnakenburg; Wim van Gemert; Ludger Staib (MDPI AG, 2022)
A pediatric robotic pyeloplasty has been performed with the Senhance® robotic system for the first time in January 2021 on a 1.5-year-old girl with symptomatic ureteropelvic junction stenosis. A Senhance® robotic system (Asensus Surgical® Inc., Durham, NC, USA) with three arms and 5 mm instruments was used, providing infrared eye tracking of the 5 mm camera and haptic feedback for the surgeon, facilitating suturing of the anastomosis and double-J stent insertion. The robotic surgery lasted 4.5 h, was uneventful and successful, without recurrence of the ureteropelvic junction obstruction after six months, and with normal development of the patient's growth and organ function. The use of the robotic system was shown to be safe and feasible; long term follow-up will be conducted subsequently in pediatric surgery.